The role of lactate in the exercise-induced human growth hormone response: evidence from McArdle disease. Issue 7 (9th January 2008) - Godfrey, R J; Whyte, G P; Buckley, J; Quinlivan, R
Abstract : Purpose: Increased blood lactate concentration has been suggested as a primary stimulus for the exercise-induced growth hormone response (EIGR). Patients with McArdle disease are unable to produce lactate in response to exercise and thus offer a unique model to assess the role of lactate in the EIGR. Accordingly, McArdle's patients were exercised to test the hypothesis that lactate is a major stimulus of the EIGR. Methods: 11 patients with McArdle disease (3 male, 8 female; age: 35.5 (SD 13.9) years, height: 166 (8) cm, body mass: 75.2 (13.1) kg) were recruited for the study. The patients walked initially at 0.42 m/s, increasing by 0.14 m/s per 3 min stage. Exercise was terminated when participants completed 3 minutes at 1.80 m/s or when a Borg CR10 pain scale rating of "4" was reached. Stages were separated by 60 s for capillary blood sampling for analysis of hGH and blood lactate concentration. Results: McArdle's patients' blood lactate levels remained at resting levels (0.3–1.2 mmol/l) as exercise intensity increased. Nine out of 11 participants failed to demonstrate an EIGR obtaining hGH values below the clinical definition of a response (>3 μg/l). Conclusion: The absence of an EIGR in nine out of 11 participants suggests that lactate could play a major role in the EIGR in humans.